CRISPR-Cas Systems in Bacteroides fragilis, an Important Pathobiont in the Human Gut Microbiome - Tajkarimi, Mehrdad; Wexler, Hannah M. (Frontiers in Microbiology, 2017)
Background: While CRISPR-Cas systems have been identified in bacteria from a wide variety of ecological niches, there are no studies to describe CRISPR-Cas elements in Bacteroides species, the most prevalent anaerobic bacteria in the lower intestinal tract. Bacteroides make up 25% of the total gut microbiome. B. fragilis comprises only 2% of the total Bacteroides in the gut, yet causes >70% of Bacteroides infections. The factors causing it to transition from benign resident of the gut microbiome to virulent pathogen are not well understood, but a combination of horizontal gene transfer (HGT) of virulence genes and differential transcription of endogenous genes are clearly involved. The CRISPR-Cas system is a multi-functional system described in prokaryotes that may be involved in control both of HGT and of gene regulation. Results: CRISPR elements in all strains of B. fragilis (n=109) with publically available genomes were identified. Three different CRISPR-Cas types, corresponding to Type IB, Type IIIB and Type IIC, were identified. Thirty-five strains had two CRISPR-Cas types, and three strains included all three CRISPR-Cas types in their respective genomes. The cas1 gene in the Type IIIB system encoded a reverse-transcriptase/Cas1 fusion protein rarely found in prokaryotes. We identified a short CRISPR (3 DR) with no associated cas genes; these CRISPRs were found immediately upstream of a hipA/hipB operon implicated in other bacteria in formation of persister cells. Also, blood isolates of B. fragilis did not have Type IIC CRISPR-Cas systems and had atypical Type IIIB CRISPR-Cas systems that were lacking adjacent cas genes. Conclusions: This is the first systematic report of CRISPR-Cas systems in a wide range of B. fragilis strains from a variety of sources. There are four apparent CRISPR-Cas systems in B. fragilis—three systems have adjacent cas genes. Understanding CRISPR/Cas function in B. fragilis will elucidate their role in gene expression, DNA repair and ability to survive exposure to antibiotics. Also, based on their unique CRISPR-Cas arrays, their phylogenetic clustering and their virulence potential, we are proposing that blood isolates of B. fragilis be viewed a separate subgroup.